Carta de perigo a movimentos de massa para o Morro da Polícia, Porto Alegre - RS - Lamberty, Débora (2018)
An area of hazard of mass movement corresponds to an area prone to the occurrence of a physical event that can cause property damage, social and economic disturbance and even loss of life, resulting from natural or human activity. In the urban area of the Brazilian cities, the mass movements often are conditioned by the ground natural properties and by the human interventions that potentiate the occurrence of the processes. In Porto Alegre, previous works show the occurrence of mass movements. The main objective of this dissertation is to analyze the hazard of mass movements in Morro da Polícia, located in the city of Porto Alegre, State of Rio Grande do Sul. The specific objectives include understanding the conditioning factors, the identification of areas with greater human intervention, the elaboration of the hazard model and the validation of the model, considering previous works already carried out in the area. The work had been developed using vector data, satellite images and aerial photographs, using geoprocessing techniques in a GIS environment. A susceptibility model was generated, classified in high, medium and low grade, based on natural factors: angle of slope, slope shape and distance of lineaments. The evaluation of the human action had as its starting point the data of density and the pattern of occupation. The susceptibility model was added to the human component, resulting in a hazard model that classified the occupied area of the Morro da Polícia in high, medium and low grade of hazard. The high-grade areas are concentrated in the middle third of the slopes, in agreement with the greater slopes angle and with the areas of disordered occupation. The low-grade areas correspond to the foothills of the slopes, with smooth slope angle, away from the structural lineaments and with orderly to disorderly with low density occupation. The result allowed to obtain the hazard model that indicates the critical areas for the deflagration of the mass movements, showing a good match when compared with previous works developed in Morro da Polícia in Porto Alegre.